Intergrated farming and marketing system - Muigai,Njehu Charles (Meru: Njehu Charles Muigai, 2013)
The process of marketing, finding customers and the whole process of farm production remains a challenge to farmers. This is mostly because of lack of sufficient information on current market, lack of defined market places and appropriate farming methods from the area officers and the farmers associations. This leads to price fluctuations, value loss of the produce as some of them are perishable and are of poor yields due to lack of advice from the cooperative, related boards and scarce information providers on modern farming methodologies. By the end of the day, the farmer will go for the least prices, experience increased waste, thus a reduction in produce causing low living standards and rise in poverty level. Therefore, there is a need for more reliable, efficient and automated system to help farmers on finding information on modern farming methods, current market status and accessing planning advice from fellow farmers and experts.
A project submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Computer Science.